Patients’ Needs for Care in Public Mental Health: Unity and Diversity of Self-Assessed Needs for Care - Bellier-Teichmann, Tanja; Golay, Philippe; Bonsack, Charles; Pomini, Valentino (Frontiers in Public Health, 2016)
Purpose. Needs assessment is recognized to be a key element of mental health care. Patients tend to present heterogeneous profiles of needs. However, there is no consensus in previous research about how patients’ needs are organized. This study investigates both general and specific dimensions of patients’ needs for care. Methods. Patients’ needs were assessed with ELADEB, an 18-domain self-report scale. The use of a self-assessment scale represents a unique way of obtaining patients’ perceptions. A patient-centered psychiatric practice facilitates empowerment as it is based on the patients’ personal motivations, needs and wants. 471 patients’ profiles were analyzed through exploratory factor analysis. Results. A four-factor bi-factor model, including one general factor and three specific factors of needs was most adequate. Specific factors were: (a) ‘finances’ and ‘administrative tasks’; (b) ‘transports’, ‘public places’, ‘self-care’, ‘housework’ and ‘food’; (c) ‘family’, ‘children’, ‘intimate relationships’ and ‘friendship’. Conclusions. As revealed by the general factor, patients expressing urgent needs in some domains are also more susceptible to report urgent needs in several other domains. This general factor relates to high versus low utilizers of public mental healthcare. Patients also present specific needs in life domains, which are organized in three dimensions: management; functional disabilities; familial and interpersonal relationships. These dimensions relate to the different types of existing social support described in the literature.